Effectiveness of preoperative ketamine gargle to reduce postoperative sore throat in adult patients undergoing surgery with endotracheal tube; systematic review and meta-analysis of randomized control trials - Molla Amsalu Tadesse; Agmuas Asichale Alimawu; Fetene Seyoum Kebede; Eniyew Assimie Alemu; Ludwig Matrisch; Desta Oli Waktasu (BMC Anesthesiology)
Abstract Background Postoperative sore throat is a frequent and distressing complication caused by airway instrumentation during general anesthesia. The discomfort can lead to immediate distress, delayed recovery and reduce patient satisfaction. The objective of this study was to determine the effectiveness of preoperative ketamine gargle on the occurrence of postoperative sore throat among adult patients who underwent surgery under general anesthesia with endotracheal tube. Method PubMed, Cochrane Library, Google Scholar, and World Clinical Trial Registry were searched to find the eligible randomized control trials comparing the effect of preoperative ketamine gargle and placebo gargle on the occurrence of postoperative sore throat after surgery with endotracheal tube in adult patients. We utilized Review Manager Version 5.4 to perform statistical analyses. Cochrane risk of bias tool for randomized control trials was used to assess the risk of bias of included studies. We explored heterogeneity using the I2 test. In addition to this, subgroup analysis, and sensitivity analysis was conducted to confirm the robustness of findings. The risk of publication bias was tested using funnel plot Pooled risk ratio along with 95% confidence interval (CI) was used to analyze the outcome. Result In the present systematic review and metanalysis, seventeen [17] randomized controlled trials (RCTs) with 1552 participants were included. Compared with placebo, preoperative ketamine gargle is effective to reduce postoperative sore throat (RR = 0.48; 95%CI [0.45, 0.52] in adult patients undergoing surgery under general anesthesia with endotracheal tube. Conclusion Preoperative ketamine gargle before induction of general anesthesia is effective to reduce the occurrence of postoperative sore throat in adult patients undergoing surgery under general anesthesia with an endotracheal tube. Further studies with large sample size, better study quality and optimal reporting could be conducted to determine the long-term efficacy and safety of ketamine gargle in different surgical populations.